Lived experience experts: a name created by us for us - Vázquez, Esmeralda; Kim, Michelle; Santaella, Maria E (Expert review of hematology, 2023)
Plain Language SummaryPeople affected by a medical disorder, usually called patients, develop a very special expertise by living with it every day. They know, better than anyone else, how it affects their lives, what they go through to get a diagnosis and treatment, how treatments affect them, how symptoms or side effects impact their daily life, and what it is like to interact with the health care system. The people who share their lives, usually close family members like parents, partners, or siblings, develop similar knowledge. When it comes to research, patients are usually seen only as subjects. In the recent National Hemophilia Foundation State of the Science Research Summit and the subsequent National Research Blueprint project, people with inherited bleeding disorders and their family members were invited to participate in creating an agenda of the most important research that needs to be done, and in designing the approach to do the research. As full members of State of the Science Working Groups, and in leadership roles in the National Research Blueprint, they realized they needed a title that recognizes and clearly communicates their unique expertise, so that the people they work with understand what they bring to the table. They chose the term lived experience expert (LEE). Especially in rare disorders, LEEs have unique, valuable expertise to contribute to all stages of research (e.g. planning and designing, participating and recruiting participants, communicating its importance and results). Including LEEs in leadership roles will make research stronger.